Genetic Evolution of Mycobacterium abscessus Conferring Clarithromycin Resistance during Long-Term Antibiotic Therapy - Bing Li; Qi Guo; Yanhua Mao; Yuzhen Zou; Yongjie Zhang; Zhemin Zhang; Haiqing Chu (Canadian Respiratory Journal)
Objectives. Clarithromycin is recommended as the core agent for treating M. abscessus infections, which usually calls for at least one year of treatment course, facilitating the development of resistance. This study aimed to identify the underlying mechanism of in vivo development of clarithromycin resistance in M. abscessus clinical isolates. Methods. M. abscessus isolates from patients with lung infections during long-term antibiotic therapy were longitudinally collected and sequenced. PFGE DNA fingerprinting was used to confirm the genetic relationships of the isolates. Whole genome comparative analysis was performed to identify the genetic determinants that confer the clarithromycin resistance. Results. Three pairs of initially clarithromycin-susceptible and subsequently clarithromycin-resistant M. abscessus isolates were obtained. We found that the clarithromycin-resistant isolates emerged relatively rapidly, after 4–16 months of antibiotic therapy. PFGE DNA fingerprinting showed that the clarithromycin-resistant isolates were identical to the initial clarithromycin-susceptible ones. Whole genome sequencing and bioinformatics analysis identified several genetic alternations in clarithromycin-resistant isolates, including genes encoding efflux pump/transporter, integral component of membrane, and the tetR and lysR family transcriptional regulators. Conclusion. We identified genes likely encoding new factors contributing to clarithromycin-resistance phenotype of M. abscessus, which can be useful in prediction of clarithromycin resistance in M. abscessus.